2021
DOI: 10.1016/j.apnu.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and burnout in healthcare students and inpatient psychiatric nurses: A between-groups study of two populations

Abstract: Background Stressful environments can have significant effects on an individual and lead to burnout. Psychological consequences of burnout include trauma reactions, depression, anxiety and substance use disorders. Resilience, a protective mechanism can mitigate the negative impact of burnout. Method This study utilizes an exploratory correlational design to determine whether or not there is 1) a similar correlation between resilience and burnout between psychiatric nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 67 publications
(83 reference statements)
2
38
0
2
Order By: Relevance
“…Furthermore, emotional exhaustion predicted general health better than the total score of burnout alone. This is consistent with previous studies that considered emotional exhaustion as the core dimension of burnout ( Pavlakis et al, 2010 ; Abraham and Jacobowitz, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, emotional exhaustion predicted general health better than the total score of burnout alone. This is consistent with previous studies that considered emotional exhaustion as the core dimension of burnout ( Pavlakis et al, 2010 ; Abraham and Jacobowitz, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Such a correlation also appeared in the studies by Aslan et al, 13 and Abram and Jacobowitz. 18 They found that high stress is the main cause of burnout in the long term. The results of the studies included in this paper also reveal a negative relationship between students’ burnout and their subjective well-being (H 3 ) in the process of adaptation to distance learning, hence supporting the findings of Abram and Jacobowitz.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies included in this paper also reveal a negative relationship between students’ burnout and their subjective well-being (H 3 ) in the process of adaptation to distance learning, hence supporting the findings of Abram and Jacobowitz. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience is defined as the process of, capacity for, or outcome of successful adaptation despite challenging or threatening circumstances [ 8 ], hence an ability for flexible adaptation to challenges [ 9 ]. It has an influence on other terms pertaining to an individual’s or a group’s mental state—well-being and burnout [ 10 , 11 ]. Well-being is successful and fulfilling performance in the psychological and physical domains of life [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%